Comparison of FT-Raman and FT-NIR spectroscopy for distinguishing between two honey PDOs - Pedro, Soraia (2024)
Vibrational spectroscopy has demonstrated high applicability for honey analysis, offering rapid, non-destructive and accurate methods for assessing its chemical composition, identifying different honey regions and ensuring authenticity. In this study, we compare the usefulness of FT-Raman and FT-NIR spectroscopy techniques in distinguishing between two Protected Designation of Origin (PDO) of honey, name quality, determined according to the standard methods of the International Honey Commission including acidity, pH, moisture, water activity (aw), electrical conductivity (EC), total polyphenols (TPC), total flavonoid content (TFC), and CIELAB color (L*, a*, b*), as well as the color in PFUND scale. The values observed for the analytical parameters are all in accordance with legal limits.